Chemistry at the rim: Differentiation of isomeric open-cage fullerenes by MALDI-LIFT and ESI-MS/MS - Nye, Leanne C.; Hitzenberger, Jakob; Roubelakis, Manolis M.; Orfanopoulos, Michael; Drewello, Thomas (International Journal of Mass Spectrometry, 2019)
Isomeric open-cage fullerenes ( OCFs) are studied by MALDI-LIFT. The two types of isomers feature different connectivities of the heteroatoms at the rim of the orifice to the fullerene cage. The molecular ions (radical cations, M+.) are generated by electron transfer MALDI, using DCTB as the matrix. The resulting LIFT spectra are indistinguishable. The alternative use of pencil lead is found inferior as a matrix but proves an exceptionally facile method of creating sodium and potassium adducts. The fragmentation of these metallated OCFs reveals different fragmentation pathways allowing the differentiation of the OCF isomers. This is evidently caused by the different interactions of the metal cation with the heteroatoms at the rim of the orifice. Additionally, the influence of the functionalization and isomer structure on the sodium ion affinity (SIA) is analysed by the kinetic method investigating the dissociations of sodium-bound hetero-dimers in electrospray ionization/ collision-induced dissociation (ESI-CID) experiments. (C) 2018 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2019-02-21

Direct Covalent Coupling of Porphyrins to Graphene - Dasler, Daniela; Schäfer, Ricarda; Minameyer, Martin; Hitzenberger, Jakob; Hauke, Frank; Drewello, Thomas; Hirsch, Andreas (Journal of the American Chemical Society, 2017)

Dithiafulvenyl-Extended N-Heterotriangulenes and Their Interaction with C60: Cooperative Fluorescence - Gliemann, Bettina; Strauß, Volker; Hitzenberger, Jakob; Dral, Pavlo O.; Hampel, Frank; Gisselbrecht, Jean-Paul; Drewello, Thomas; Thiel, Walter; Guldi, Dirk Michael; Kivala, Milan (Chemistry - A European Journal, 2017)
We describe the synthesis as well as the electronic and photophysical characterization of novel N-heterotriangulene derivatives decorated with methoxycarbonyl- and methyl-sulfanyl-substituted dithiafulvenyl moieties. The association of these electron-rich compounds with fullerene C60 as electron acceptor was investigated by means of photophysical, voltammetric, and mass spectrometric methods and rationalized by DFT calculations. Importantly, light-induced interactions between the dithiafulvene-substituted N-heterotriangulene bearing methoxycarbonyl substituents with C60 leads to cooperative fluorescence. Quantitative Job plot analyses by means of fluorescence spectroscopy and voltammetry confirm a 1:1 association with binding constants in the order of 104 m-1. Supportive results for the supramolecular assembly of both N-heterotriangulenes with C60 were obtained by ESI mass spectrometric investigations in the gas phase.
EAM Import::2019-03-13

Gas-Phase Transformation of Fluorinated Benzoporphyrins to Porphyrin-Embedded Conical Nanocarbons - Lungerich, Dominik; Hitzenberger, Jakob; Ruppel, Michael; Döpper, Tibor; Witt, Matthias; Ivanovic-Burmazovic, Ivana; Görling, Andreas; Jux, Norbert; Drewello, Thomas (Chemistry - A European Journal, 2020)
Geodesic nitrogen-containing graphene fragments are interesting candidates for various material applications, but the available synthetic protocols, which need to overcome intrinsic strain energy during the formation of the bowl-shaped skeletons, are often incompatible with heteroatom-embedded structures. Through this mass spectrometry-based gas-phase study, we show by means of collision-induced dissociation experiments and supported by density functional theory calculations, the first evidence for the formation of a porphyrin-embedded conical nanocarbon. The influences of metalation and functionalization of the used tetrabenzoporphyrins have been investigated, which revealed different cyclization efficiencies, different ionization possibilities, and a variation of the dissociation pathway. Our results suggest a stepwise process for HF elimination from the fjord region, which supports a selective pathway towards bent nitrogen-containing graphene fragments.
CRIS-Team Scopus Importer:2020-09-11
Keywords: annulenes; collision-induced dissociation; C−F activation; mass spectrometry; polycyclic aromatic hydrocarbons; porphyrinoids

Influence of electronic and molecular structure on the fragmentation dynamic of even-electron carbocationic triangulenes and helicenes in the gas phase - Hitzenberger, Jakob; Uhl, Agnes; Schatz, Jürgen; Drewello, Thomas (Journal of Mass Spectrometry, 2017)
Stable, long-lived organic cations are directly transferred by electrospray ionization (ESI) from solution into the gas phase where their collision-induced dissociations (CID) are studied by tandem mass spectrometry. Three related types of triphenyl carbenium ions are investigated, in which the meta positions are either substituted by methoxy groups or tertiary nitrogen bridges, including tetramethoxyphenylacridinium (TMPA+), dimethoxyquinacridinium (DMQA+), and triazatriangulenium (TATA+) cations. These ions are triangular in shape with increasing degrees of planarity. Fragmentation occurs at the periphery of the triangular molecule, involving the methoxy groups and the substituent of the nitrogen bridge. Each initial precursor cation is an even electron (EE) system and shows competing dissociations into both even (EE) and odd electron (OE) fragment ions. The latter reaction is a breach of the classic ‘even-electron rule’ in mass spectrometry. While the EE fragment dissociates similar to the precursor, the OE fragment ion shows a rich radical-induced fragmentation pattern. Two driving forces direct the fragmentation of the EE precursor ion toward OE fragment ions, including the release of stabilized radicals and the extension of the π-system by increasing planarization of the triangulene core.
Keywords: Triangulenium salt; mass spectrometry

Molecular Layer Deposition from Dissolved Precursors - Fichtner, Johannes; Wu, Yanlin; Hitzenberger, Jakob; Drewello, Thomas; Bachmann, Julien (ECS Journal of Solid State Science and Technology, 2017)
We present a procedure for growing thin films of an organic polyamid material based on a cyclic repetition of two consecutive, complementary, self-limiting surface reactions. The molecular compounds that react with the surface are dissolved in an organic solvent. This new method exemplifies how atomic layer deposition (ALD) and molecular layer deposition (MLD) can benefit from being transferred from the gas phase to the liquid phase, given that a broad variety of advantageous reagents are only available in dissolved form. (c) The Author(s) 2017. Published by ECS. All rights reserve

Molecular layer deposition from dissolved precursors - Fichtner, Johannes; Wu, Yanlin; Hitzenberger, Jakob; Drewello, Thomas; Bachmann, Julien (ECS Transactions, 2017)
We present a procedure for growing thin films of an organic polyamid material based on a cyclic repetition of two consecutive, complementary, self-limiting surface reactions. The molecular compounds that react with the surface are dissolved in an organic solvent. This new method exemplifies how atomic layer deposition (ALD) and molecular layer deposition (MLD) can benefit from being transferred from the gas phase to the liquid phase, given that a broad variety of advantageous reagents are only available in dissolved form.
CRIS-Team Scopus Importer:2022-04-14

Stability of Odd- Versus Even-Electron Gas-Phase (Quasi)Molecular Ions Derived from Pyridine-Substituted N-Heterotriangulenes - Hitzenberger, Jakob; Dral, Pavlo O.; Meinhardt, Ute; Clark, Timothy; Thiel, Walter; Kivala, Milan; Drewello, Thomas (ChemPlusChem, 2017)
Electrospray ionisation of N-heterotriangulenes (i.e., dimethyl-methylene-bridged triphenylamines) with up to three pyridyl groups at their periphery, produces the true radical cation ([M](+center dot)) and the protonated molecule ([M+H](+)) simultaneously. These ions are studied as model systems to illustrate the stability alternation of odd-versus even-electron ions in energy-dependent collision-induced dissociation (CID) experiments. All ions show the same fragmentation pattern, the consecutive loss of three methyl radicals ((CH3)-C-center dot) from the dimethylmethylene bridges of the central triangulene core. [M](+center dot) ions dissociate at much lower collision energies than their [M+H](+) counterparts. The radical cation forms a singlet fragment with an extended aromatic system that is energetically favoured. Ab initio and density functional theory calculations support this interpretation and allow the assignment of the electronic structure of the fragment ions. Consecutive collision-induced dissociations provide a better match with theory when studied with an ion trap, rather than a linear quadrupole. This is attributed to the resonant nature of the excitation of intermediate ions.
Keywords: ab initio calculations; collision-induced dissociation; density functional calculations; electrospray ionisation; mass spectrometry; N-heterotriangulenes